The Implementation of the Mathematics Curriculum in Basic and Secondary Education in Timor-Leste: Examining Its Developments and Challenges - Lopes, Venâncio (CV. Green Publisher Indonesia, 2025)
This article aims to identify and describe the developments and challenges encountered by mathematics teachers during the implementation of the Basic and Secondary Education Curriculum in Timor-Leste. The methodology adopted in this study follows a quantitative approach guided by a descriptive-interpretive paradigm. Data were collected through a closed-ended questionnaire, and the participants consisted of mathematics teachers who were still actively fulfilling their roles as learning facilitators in the 2024 academic year. The study involved 30 teachers in total, with 15 teachers each selected from the municipalities of Baucau and Bobonaro. Quantitative analysis was conducted to identify developments and obstacles related to the implementation of the mathematics curriculum at the basic and secondary levels in Timor-Leste. According to the results, in terms of planning, the teachers acknowledged that the mathematics curriculum serves as one of the fundamental elements guiding their classroom work. Regarding teaching practices, they viewed the curriculum as a document that organizes learning experiences in the classroom. In terms of learning assessment, teachers argued that the curriculum and assessment are complementary tools designed to ensure the quality of education. Furthermore, the results also revealed several obstacles faced by teachers, such as the lack of technological resources—including calculators, computers, and internet access—to support the effective implementation of the mathematics curriculum in basic and secondary schools in Timor-Leste